Circular RNA_0000326 promotes bladder cancer progression via microRNA-338-3p/ETS Proto-Oncogene 1/phosphoinositide-3 kinase/Akt pathway. Issue 2 (20th December 2021) - Chen, Yong; Wang, Dong; Shu, Tao; Sun, Kangwei; Zhao, Jianbo; Wang, Min; Huang, Yi; Wang, Ping; Zheng, Hang; Cai, Zhixuan; Yang, Zengyue
ABSTRACT: Circular RNAs (circRNAs) play a pivotal regulatory role in bladder cancer (BC) occurrence and progression. The expression level, role and mechanism of circ_0000326 in BC remain unknown. In the present study, quantitative reverse transcription-polymerase chain reaction (qRT-PCR) was conducted to evaluate the expressions of circ_0000326, microRNA-338-3p (miR-338-3p) and ETS Proto-Oncogene 1(ETS1) mRNA in BC tissues and cell lines. Cell counting kit-8 (CCK-8) assay, wound healing assay and flow cytometry were used to detect the impacts of circ_0000326 on BC cell growth, migration and apoptosis. Western blot was used to detect the expressions of ETS1, phospho-phosphoinositide-3 kinase (p-PI3K), phospho-AKT, PI3K and AKT protein. Gene ontology (GO) analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis were performed to analyze the biological function of ETS1 in BC. Here, we found that circ_0000326 expression was significantly elevated in BC cell lines and tissues, and circ_0000326 could promote BC cell growth and migration, and inhibit apoptosis. Dual-luciferase reporter gene assay confirmed that circ_0000326 and ETS1 could bind directly to miR-338-3p. Furthermore, circ_0000326 sponged miR-338-3p and up-regulated ETS1 expression. ETS1 was associated with the activation of PI3K/AKT pathway. Moreover, circ_0000326 could activate PI3K/AKT pathway by miR-338-3p/ETS1 axis. Collectively, circ_0000326/miR-338-3p/ETS1/PI3K/AKT pathway is involved in regulating BC progression.